Ideology Critique in the Age of Algorithmic Governance - Christian Filk (Medienimpulse)
Christian Filk develops ideology critique as essential for media pedagogy in the platformized society. Drawing on German and English scholarship, he analyzes how digital platforms naturalize neoliberal power relations in educational contexts through a three-dimensional framework examining discursive narratives, structural arrangements, and subjectivation effects. Against platform capitalism’s hegemonic logic, Filk proposes critical-reflexive media pedagogy based on four normative principles: digital maturity, technological solidarity, digital justice, and ecological sustainability. His article integrates German and international research, demonstrating convergence in critical approaches to digital capitalism. He combines rigorous analysis with transformative practices like algorithmic deconstruction and commons-based production, transcending conventional digital literacy approaches. Filk concludes that realizing this critical-reflexive practice requires sustained international dialogue and coalition building across disciplines and geopolitical boundaries.